2017
DOI: 10.1161/jaha.116.005273
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Heart Failure US Ambulatory Cardiology Practices and the Potential for Uptake of Catheter Ablation: An National Cardiovascular Data Registry (NCDR ® ) Research to Practice (R2P) Project

Abstract: BackgroundAtrial fibrillation (AF) and heart failure with reduced ejection fraction frequently coexist. The AATAC (Ablation versus Amiodarone for Treatment of persistent Atrial fibrillation in patients with Congestive heart failure and an implantable device) trial suggests that catheter ablation may benefit these patients. However, applicability to contemporary ambulatory cardiology practice is unknown.Methods and ResultsUsing the outpatient National Cardiovascular Data Registry® Practice Innovation and Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Management can vary widely according to presentation and should be individualized since treatments shown to be effective in one or other condition alone, may give rise to safety or efficacy issues in an individual patient. Several recent trials have suggested a preferential role for primary catheter ablation of AF in select AF patients with HF compared to medical therapy alone 296–298 . Treatment of AF by either rate or rhythm control may reverse the cardiomyopathy and improve clinical HF substantially in selected patients.…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Atrmentioning
confidence: 99%
“…Management can vary widely according to presentation and should be individualized since treatments shown to be effective in one or other condition alone, may give rise to safety or efficacy issues in an individual patient. Several recent trials have suggested a preferential role for primary catheter ablation of AF in select AF patients with HF compared to medical therapy alone 296–298 . Treatment of AF by either rate or rhythm control may reverse the cardiomyopathy and improve clinical HF substantially in selected patients.…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Atrmentioning
confidence: 99%
“…Upon the reestablishment of SR, HF patients potentially benefit from atrial contraction improving diastolic filling and the restoration of atrio‐ventricular sequential activation. Conclusively, a relief of HF related symptoms was observed upon cardiac rhythm control . However, until recently, randomized trials failed to prove that the hemodynamic benefits of rhythm control strategies translate into decreased mortality.…”
Section: Atrial Fibrillation and Heart Failurementioning
confidence: 99%
“…Another important trial suggesting benefits of ablation in HF patients suffering from AF was AATAC (Ablation vs Amiodarone for Treatment of Persistent Atrial Fibrillation in Patients with Congestive Heart Failure and an Implanted Device), published in 2016 . It was an open‐label, randomized and multicenter trial.…”
Section: Atrial Fibrillation Catheter Ablation In Patients With Heartmentioning
confidence: 99%
See 2 more Smart Citations